Evaluation to Reduce Occupational Risk In Excavator Manufacturing - Yuliani, Euis Nina Saparina; Prakoso, Galih; Iridiastadi, Hardianto; Adiatmika, I Putu Gede (Journal of A Sustainable Global South; Vol 4 No 1 (2020): February 2020DO - 10.24843/jsgs.2020.v04.i01.p06, 2020)
Musculoskeletal disorders often occur in non-ergonomic work postures. The research was conducted in the process of installing an air cleaner workstation for the excavator’s assembly at a heavy equipment manufacturing company. In the installation process, the operator must lift, hold and install the component with weight 12 kg, using the limbs manually without any tools. The objective of this study is to conduct an ergonomic evaluation by assessing the risk of musculoskeletal disorders and provide recommendations for improvement in order to reduce operator musculoskeletal injuries. To determine the level of risk of the job will be used the Rapid Entire Body Assessment method. The results of this study are R.E.B.A scores obtained which is 11, with a very high level of risk, and must be immediately corrected. Ergonomic intervention as a recommendation for improvements that support the work of the operator, is making jigs to help the installation process. After implementation, the REBA score dropped to 3 or decreases by around 67% from the initial risk Index Terms — ergonomics intervention, musculoskeletal disorders, rapid entire body assessment